Effect of genotype and genotype by environment interaction on total cyanide content, fresh root, and starch yield in farmer-preferred cassava landraces in Tanzania - Mtunguja, M.K.; Laswai, H.S.; Kanju, E.; Ndunguru, J.; Muzanila, Y.C. (Wiley, 2016)
High starch yield is the most important trait for commercialized cassava starch production. Furthermore, cyanide present in cassava roots poses a health challenge in the use of cassava for food. Cassava genotypes have varying maturity periods that are also environmental dependent. This study aimed at identifying suitable cultivars and optimum time of harvest to maximize starch production across three environments. The study found significant difference between genotypes, locations, harvest period, and all the interactions (P ≤ 0.001) for all traits analyzed. Kiroba recorded high starch yields of 17.4, 12.7, and 8.2 t ha−1 at Chambezi, Amani, and Magadu, respectively. Kilusungu recorded highest cyanide content of 300–400 ppm across all locations but Kiroba recorded highest values of 800 ppm, 15 months after planting at Chambezi. Genotype by environment (GGE) biplot analysis revealed that Kiroba was a superior cultivar in terms of starch yield. Kilusungu recorded highest cyanide content and average starch yield, therefore suitable for use in starch production. The study confirmed effect of genotype and genotype by environment interaction, Kiroba cultivar was superior in terms of starch yield and maximum starch yield was obtained at 9 months after planting. Nyamkagile and Kibandameno had the lowest cyanide content across all environments.